2016
DOI: 10.1007/s10068-016-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Free and bound form bioactive compound profiles in germinated black soybean (Glycine max L.)

Abstract: This study investigated the transition between the free and bound forms of functional compounds in germinated black soybean. Black soybean was germinated at 25°C over 6 days and then the free and bound forms of functional compounds were extracted. Total free polyphenol, flavonoid, and phenolic acid contents in raw black soybean increased from 1.03 mg GAE/g, 0.29 mg CE/g, and 315.67 μg/g to 1.44mg GAE/g, 0.64mg CE/g, and 511.01 μg/g, respectively, by 4 days after germination. Changes to phenolic acid compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…The phenolic acid composition of each extract was determined by high-performance liquid chromatography (HPLC), as described by Kim et al 16 We used an ODS column (5 μm, 4.6 × 250 mm; Agilent Technologies, Santa Clara, CA, USA). Gradient elution was performed with solvent A (water with 0.1% (v/v) acetic acid) and solvent B (acetonitrile with 0.1% (v/v) acetic acid).…”
Section: Quantification Of Phenolic Acid Compoundsmentioning
confidence: 99%
“…The phenolic acid composition of each extract was determined by high-performance liquid chromatography (HPLC), as described by Kim et al 16 We used an ODS column (5 μm, 4.6 × 250 mm; Agilent Technologies, Santa Clara, CA, USA). Gradient elution was performed with solvent A (water with 0.1% (v/v) acetic acid) and solvent B (acetonitrile with 0.1% (v/v) acetic acid).…”
Section: Quantification Of Phenolic Acid Compoundsmentioning
confidence: 99%
“…e phenolic acid composition of each extract was determined via HPLC as described by Kim et al [21]. e column was employed an ODS column (5 μm, 4.6 × 250 mm; Agilent Technologies, Santa Clara, CA, USA).…”
Section: Measurement Of Individual Phenolic Acid Levelsmentioning
confidence: 99%
“…These findings are supported by those previously reported by other authors, who also observed twofold increase in phenolic compounds of quinoa sprouts obtained after 72-82 h of germination at 10-20°C (Alvarez-Jubete et al, 2010; Carciochi et al, 2014). The enhancement observed in phenolic levels during quinoa germination can be attributed to their novo synthesis during this process (Kim et al, 2016). However, quinoa seeds exhibit a high content of insoluble phenolics that are covalently found to cell wall structural components and rod-shaped structural proteins (Tang et al, 2016).…”
Section: Impact Of Germination Conditions On Tpc Content Of Quinoa Spmentioning
confidence: 99%